Westonci.ca is your trusted source for finding answers to all your questions. Ask, explore, and learn with our expert community. Discover reliable solutions to your questions from a wide network of experts on our comprehensive Q&A platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To solve the system of equations using elimination, let's follow a step-by-step approach:
### Given System of Equations:
[tex]\[ \begin{array}{c} 3g + 4h = 24 \\ -g + 2h = 2 \end{array} \][/tex]
### Step 1: Eliminate One Variable
To eliminate the variable [tex]\( g \)[/tex], we will perform some operations on these equations. Let's start by eliminating [tex]\( g \)[/tex] from the second equation.
#### Adjust the Second Equation:
Multiply the entire second equation by 3 so that the coefficients of [tex]\( g \)[/tex] in both equations have the same magnitude but opposite signs:
[tex]\[ -3g + 6h = 6 \][/tex]
The system now becomes:
[tex]\[ \begin{array}{c} 3g + 4h = 24 \\ -3g + 6h = 6 \end{array} \][/tex]
### Step 2: Add the Equations to Eliminate [tex]\( g \)[/tex]
Add the two equations together:
[tex]\[ (3g + 4h) + (-3g + 6h) = 24 + 6 \][/tex]
[tex]\[ 3g - 3g + 4h + 6h = 30 \][/tex]
[tex]\[ 0g + 10h = 30 \][/tex]
So, the resulting equation is:
[tex]\[ 10h = 30 \][/tex]
### Step 3: Solve for [tex]\( h \)[/tex]
Divide both sides by 10:
[tex]\[ h = \frac{30}{10} = 3 \][/tex]
### Step 4: Substitute [tex]\( h \)[/tex] Back into One of the Original Equations
Now, we need to find the value of [tex]\( g \)[/tex]. Substitute [tex]\( h = 3 \)[/tex] into the second original equation [tex]\( -g + 2h = 2 \)[/tex]:
[tex]\[ -g + 2(3) = 2 \][/tex]
[tex]\[ -g + 6 = 2 \][/tex]
Subtract 6 from both sides:
[tex]\[ -g = 2 - 6 \][/tex]
[tex]\[ -g = -4 \][/tex]
Multiply both sides by -1:
[tex]\[ g = 4 \][/tex]
### Step 5: State the Solution
The solution to the system of equations is the ordered pair [tex]\( (g, h) \)[/tex]. Thus, in alphabetical order:
[tex]\[ (g, h) = (4, 3) \][/tex]
The correct answer is:
[tex]\[ (4, 3) \][/tex]
### Given System of Equations:
[tex]\[ \begin{array}{c} 3g + 4h = 24 \\ -g + 2h = 2 \end{array} \][/tex]
### Step 1: Eliminate One Variable
To eliminate the variable [tex]\( g \)[/tex], we will perform some operations on these equations. Let's start by eliminating [tex]\( g \)[/tex] from the second equation.
#### Adjust the Second Equation:
Multiply the entire second equation by 3 so that the coefficients of [tex]\( g \)[/tex] in both equations have the same magnitude but opposite signs:
[tex]\[ -3g + 6h = 6 \][/tex]
The system now becomes:
[tex]\[ \begin{array}{c} 3g + 4h = 24 \\ -3g + 6h = 6 \end{array} \][/tex]
### Step 2: Add the Equations to Eliminate [tex]\( g \)[/tex]
Add the two equations together:
[tex]\[ (3g + 4h) + (-3g + 6h) = 24 + 6 \][/tex]
[tex]\[ 3g - 3g + 4h + 6h = 30 \][/tex]
[tex]\[ 0g + 10h = 30 \][/tex]
So, the resulting equation is:
[tex]\[ 10h = 30 \][/tex]
### Step 3: Solve for [tex]\( h \)[/tex]
Divide both sides by 10:
[tex]\[ h = \frac{30}{10} = 3 \][/tex]
### Step 4: Substitute [tex]\( h \)[/tex] Back into One of the Original Equations
Now, we need to find the value of [tex]\( g \)[/tex]. Substitute [tex]\( h = 3 \)[/tex] into the second original equation [tex]\( -g + 2h = 2 \)[/tex]:
[tex]\[ -g + 2(3) = 2 \][/tex]
[tex]\[ -g + 6 = 2 \][/tex]
Subtract 6 from both sides:
[tex]\[ -g = 2 - 6 \][/tex]
[tex]\[ -g = -4 \][/tex]
Multiply both sides by -1:
[tex]\[ g = 4 \][/tex]
### Step 5: State the Solution
The solution to the system of equations is the ordered pair [tex]\( (g, h) \)[/tex]. Thus, in alphabetical order:
[tex]\[ (g, h) = (4, 3) \][/tex]
The correct answer is:
[tex]\[ (4, 3) \][/tex]
We hope this was helpful. Please come back whenever you need more information or answers to your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.